Fuelling insecurity : energy securitization in Azerbaijan - Ganz, Aurora (Bristol : Bristol University Press, 2022)
This book examines the extensive network of security professionals and the wide range of practices that have spread in Azerbaijan's energy sector. It unpacks the interactions of state, supra-state, and private security organisations, and argues that energy security has enabled and normalised a coercive way of exercising power.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Energy security -- Azerbaijan; Energy security -- Political aspects -- Azerbaijan; Energy industries -- Azerbaijan; Energy industries -- Corrupt practices -- Azerbaijan; Private security services -- Azerbaijan; Energy policy -- Azerbaijan; Azerbaijan -- Politics and government